A journey through the cell
This two-volume set combines live-action video, colorful computer graphics and animations, and interviews with scientists to introduce students to ideas central to understanding cells and their profound role in the living world. Viewable/printable instructor's guides are available online. Correlates to the National Science Education Standards developed by the National Academies of Science and Project 2061 Benchmarks for Science Literacy from the American Association for the Advancement of Science. A Cambridge Educational Production. 2-part series, 20 minutes each.